2018
DOI: 10.1039/c8cp00358k
|View full text |Cite
|
Sign up to set email alerts
|

Effect of water/glycerol polymorphism on dynamic nuclear polarization

Abstract: A paramount feature of robust experimental methods is acquiring consistent data. However, in dynamic nuclear polarization (DNP), it has been observed that the DNP-induced NMR signal enhancement of nominally the same sample can vary between different experimental sessions. We investigated the impact of various freezing conditions on the DNP results for a standard sample, a 50/40/10 by volume d8-glycerol/D2O/H2O solution of 40 mM 4-amino TEMPO, and found that annealing the samples 10 K above the glass transition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 36 publications
1
38
0
Order By: Relevance
“…However, it is possible that membrane phase transitions such as fluid-to-gel or other changes at low temperatures play an analogous role as the waterice transition in isotropic solvent systems. In such cases the speed of the transition can have an effect how the biradicals redistribute within the membrane interface [35,43] similar to recently published observations on water/glycerol mixtures used for DNP [66].…”
Section: Resultssupporting
confidence: 84%
“…However, it is possible that membrane phase transitions such as fluid-to-gel or other changes at low temperatures play an analogous role as the waterice transition in isotropic solvent systems. In such cases the speed of the transition can have an effect how the biradicals redistribute within the membrane interface [35,43] similar to recently published observations on water/glycerol mixtures used for DNP [66].…”
Section: Resultssupporting
confidence: 84%
“…28,29 Slower spin relaxation in glycerol containing solutions (up to 69% added glycerol) was previously shown to arise from an increase in the tumbling correlation time of the radical, which affects both the spin rotation and modulation of g-and hyperfine anisotropies. 29 While the reproducibility of solid-state DNP studies has been reported to be affected by polymorphism of water-glycerol solutions upon freezing to below 150 K, 30 to our knowledge there are no reports of polymorphism influencing relaxation properties at ambient temperatures. As our measurements are carried out exclusively at room temperature (B295 K), over 100 K above the glass transition temperature of the waterglycerol mixtures used and in a composition region not subject to reported liquid-liquid transitions, 31 polymorphism is not expected to affect our study.…”
Section: Time-resolved Epr Datamentioning
confidence: 99%
“…In this case, longer relaxation times were associated with faster buildup kinetics, as expected for narrow linewidth radicals like OX063, where rapid spin diffusion exists and the solid effect is an important component in DNP transfer. Although not tested here, annealing may prove an efficient method for reducing inhomogeneities during the freezing process 7,30‐32 …”
Section: Resultsmentioning
confidence: 99%